The economics of institutions, institutional governance and efficiency: the case of water distribution in Lower Sundays River Valley - Madigele, Patricia Kefilwe (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2015)
The institutional dynamics, policies and legislation that were prevalent during the apartheid era have left imprints that are difficult to ignore as they still dictate the interaction between different elements in the water sector to date. During the apartheid era, the formulation of policies was informed by racial segregation, resulting in a socio-economic pattern that dictated the distribution and access of resources for the people of different races in the country. Post-apartheid, the National Water Act has established the basis for management of water resources on a catchment basis (for equity, efficiency and sustainability), and the Water Services Act aims to ensure everybody has access to basic water supply and sanitation services. Regardless of the improvements in water supply to the rural sector made by the South African government, many of the current patterns of water use are still characterised by inequality, inefficiency, and inadequacy. The poor remain marginalised, and emerging farmers and poor rural communities have limited access to water resources while water continues to be used inefficiently by some farmers in the agricultural sector with few incentives to improve its water use efficiency. Despite the existence of the thriving citrus industry in the area, around 60% of people in the Sundays River Valley Municipality (SRVM) live below the poverty datum line. The inequality between the municipal populace and the commercial citrus industry is noticeable and the inequitable water redistribution is prevalent in the Lower Sundays River Valley (LSRV). The problem of disrupted water supply is prevalent in the catchment. However, there is also currently no physical shortage of water in the catchment. Therefore, the currently experienced problems with water supply in the LSRV are consequence of a lack of effective institutions and infrastructure, not of physical water scarcity. It is argued in this paper that there is a notable lack of understanding about the design of institutions for water management in developing countries. The vast majority of research on water management and access is premised on neoclassical economics ideas related to water markets and pricing among others. The neoclassical economics approach, however, does not adequately define the role of institutions in shaping the direction of water access and supply. This study uses new institutional economics (NIE) arguments to define the institutional arrangements and dynamics defining the water sector in South Africa, using the Lower Sunday River Water Users Association (LSR-WUA) as the case study. It aims at analysing the institutional governance and performance of the using equity, efficiency and effectiveness as key indicators. The various research methods employed in this study include; interpretive and post-positivist paradigms, quantitative and qualitative research, the case study research method and in-depth key informant interviews. It is concluded that that the current and future decisions made by the LSR-WUA are not entirely independent of those made in the past under Sundays River Irrigation Board (SRIB). The thesis argues that such factors as old effective networks, vested interests of commercial farmers, sunk costs towards the building of canals, among other factors, may have influenced the dependence of the LSR-WUA on the SRIB's set path. It is further concluded that the absence of contractual agreement between the LRS-WUA which acts as the bulk water supplier, and the SRVM which acts as both the water services authority (WSA) and the water service provider (WSP) creates an institutional arrangement deficiency. Such an institutional arrangement vacuum can lead to a failure of the water institutions in the catchment to provide water resources effectively. The study further argues that because the post-apartheid National Water Policy of South Africa is largely influenced by neoclassical economics foundations, the desired results in the water sector, such as equitable distribution of water resources, have not yet been fulfilled completely.
Keywords: Uncatalogued